Diagnóstico de la caja de exportación de aprovechamiento a los principales mercados de América cono Sur - Guzmán, Natalia Suárez (2011)
The diagnosis of the box-use of export to the principal markets of America (Cone South) was realized in the exporting companies Comexabril, Vanabri and Lidernegsa, for which the following aims appeared: 1. To determine the quality parameters for the export of the box-use to the principal current markets, 2. To establish the demand of the export of the box-use for the principal markets of the fruit and 3. To analyze the commercial level that the companies have in relation to the box-use and the production of this food-stuff. Basing this study on the boxes of banana of utilization exported by Ecuador to these markets on the year 2009, 2010 and the first semester of 2011. The secondhand materials were the bibliographical specialized sources and information of the studied companies and the information updated about the commercialization of the crops to determine among the evaluated variables the destinations or importing markets, the quality of the fruit, the epochs of export, the quantities of exported boxes, and the costs of export by means of the process methods of the information, statistical analyses and economic analyses, giving as conclusion that they are two boxes those that export to the Cone South, 22XUCS equally in weight, price and requirements to 22XU therefore quality must not be lower than 85 %, this one directed the Argentina and Uruguay and and 22XUCSS for Chile that differs for tolerating moderate faults, which with new official price and better specifications of quality, its production justifies and stimulates the farmer to producing a box with slight faults that do not damage the quality of the flesh, as they are established in the quality parameters of this investigation. The exports to the Cone South grew up to 7,96 % almost 1 % per year. These boxes have his high epoch in the second semester which is an advantage that compensates the low demand of the first class markets and meet benefited with better quality fruit. These markets are supplied in a regular way by few stable and serious companies that handle the major percentage in the exports, the studied companies do not have regular presence on the market due to the fact that they do not have either producers contracts nor clients who should allow them to stabilize and to guarantee long term operation.